Objective Sleep Duration in Older Adults: Results From The Irish Longitudinal Study on Ageing - Scarlett, Siobhan; Kenny, Rose (Wiley, 2020)
Objective: This study assessed the distribution and correlates of objective sleep duration in the older population in Ireland. Design: Cross-sectional study using population-derived data from wave 3 of The Irish Longitudinal Study on Ageing. Setting: Community-dwelling adults. Participants: Adults, aged 50 years and older, who wore an accelerometer for at least 4 days (N = 1533). Measurements: Sleep was measured for at least 4 days in 1533 participants using a GENEActiv wrist-worn accelerometer device. Sleep parameters included total sleep time (TST) and self-reported sleep problems. TST was categorized as short and long sleep duration using US National Sleep Foundation guidelines. Linear and multinomial logistic regression models assessed sociodemographic, health, and behavioral correlates of sleep duration. Results: Mean TST for the sample was 463 minutes (SD = 72.6 minutes). Of participants, 13.9% and 16.5% measured short and long sleep duration, respectively. TST decreased as sleep problems increased, as did durations recorded in summer compared to winter recordings. Advancing age was associated with longer sleep, as was antidepressant use. Retired/unemployed participants recorded longer TST and were more likely to record long sleep compared to employed participants. Fair/poor self-rated health and separated/divorced participants were more likely to record short sleep. Those reporting moderate or high physical activity were less likely to record short or long sleep, respectively, compared to those reporting low physical activity. Participants reporting a limiting disability were less likely to record long sleep. Conclusion: Average TST was within recommended guidelines; however, a significant subset of older adults recorded sleep duration outside of the guidelines. Independent demographic and health correlates of suboptimal sleep were identified, many of which are modifiable. Patients and clinicians should be aware of factors potentially influencing sleep patterns. Longitudinal analyses to confirm directionality of relationships with potential risk factors are warranted.
PUBLISHED
Keywords: Sleep duration; GENEActiv; Accelerometer; Older population; Actigraphy; Ageing